Risk factors for chronic postsurgical pain following minimally invasive thoracic surgery - Yongjun, Li; Weinian, Wu (Frontiers in Surgery, 2026)
ObjectiveThis study aimed to systematically identify independent risk factors for chronic postsurgical pain (CPSP) in patients undergoing minimally invasive pulmonary surgery, thereby providing an evidence-based foundation for the early identification of high-risk patients and the development of targeted preventive strategies.MethodsA case-control study design was employed. A total of 280 patients who underwent minimally invasive thoracic surgery between January 2022 and June 2024 were enrolled and categorized into a CPSP group (n = 48) and a non-CPSP group (n = 232) based on the presence of CPSP at 3 months postoperatively. Baseline characteristics, surgical features, and perioperative pain indicators—including visual analog scale (VAS) scores for pain at rest, during coughing, and during shoulder abduction assessed daily from postoperative day 1 to day 6—were prospectively collected. The occurrence of CPSP was evaluated at the 3-month follow-up. Univariate and multivariate logistic regression analyses were used to screen for independent factors influencing CPSP, and the predictive performance of these factors was assessed using receiver operating characteristic (ROC) curve analysis.ResultsUnivariate analysis revealed that preoperative anxiety, preoperative pain, surgical approach, intercostal suture, scar length, and postoperative shoulder abduction pain were significantly associated with CPSP development (P < 0.05). Multivariate logistic regression analysis ultimately identified postoperative shoulder abduction pain (OR = 1.893, 95% CI: 1.432–2.502, P < 0.001), scar length (OR = 1.240, 95% CI: 1.049–1.466, P = 0.011), and preoperative anxiety (OR = 3.089, 95% CI: 1.201–7.943, P = 0.019) as independent risk factors for CPSP, while intercostal suture (OR = 0.234, 95% CI: 0.074–0.736, P = 0.013) was an independent protective factor. Predictive performance analysis showed that postoperative shoulder abduction pain had the best predictive value [Area Under the Curve (AUC) = 0.821], with an optimal cut-off value of >3.5 points.ConclusionFor patients undergoing minimally invasive thoracic surgery, higher early postoperative (within 6 days) shoulder abduction pain scores, greater scar length, and the presence of preoperative anxiety are significant independent risk factors for developing CPSP at 3 months, whereas the use of the intercostal suture technique demonstrates a protective effect. Clinical practice should emphasize enhanced monitoring and management of postoperative shoulder abduction pain, the proactive adoption of protective surgical techniques, and attention to patients’ preoperative psychological state to effectively reduce the risk of CPSP.